Soybean breeding - Silva, Felipe Lopes da; Borém, Aluízio; Syama, Tuneo; Ludke, Willian Hytalo (Springer, 2017)
This book was written by soybean experts to cluster in a single publication the most relevant and modern topics in soybean breeding. It is geared mainly to students and soybean breeders around the world. It is unique since it presents the challenges and opportunities faced by soybean breeders outside the temperate world.